Theoretical Study of Oxidation Hydroxylation Reaction Mechanism for Nitrosodimethylamine by Oxygen Atom - Li, Lan; Li, Zong-He (Asian Journal of Chemistry, 2011)
The oxidation hydroxylation reaction mechanism of nitrosodimethylamine (NDMA) by oxygen atom has been theoretically investigated at the B3LYP/6-31G** level. It is found that the path of the oxidation of the CH bond is easier than the path involving a singlet/triplet crossing. The study of the potential surface shows that both solvent effect at B3LYP/6-31G** level and basis set effect at MP2/6-311G** level in the gas phase have no effect on the oxidation hydroxylation reaction mechanism. The oxidation hydroxylation process of nitrosodimethylamine by atomic oxygen is exothermic reaction and easy to occur.